S23 Neural respiratory drive during sleep at high altitude. (15th November 2016) - Steier, J; Cade, N; Walker, B; Moxham, J; Jolley, CJ
Abstract : Introduction: Ventilation at altitude changes due to altered levels of pO2, pCO2 and the effect on blood pH. Nocturnal ventilation is particularly exposed to these changes. We hypothesised that increasing neural respiratory drive is associated with the severity of sleep-disordered breathing at altitude. Subjects and methods: British mountaineers were studied at sea level (London, UK), and at altitude at the Aconcagua (Andes, Argentina). Neural respiratory drive (NRD) was measured as electromyogram of the diaphragm (EMGdi) overnight by a transoesophageal multi-electrode catheter (Yinghui Medical Ltd, Guangzhou, China). Following initial assessment with a polysomnography (London, UK), pulse oximetry measured oxygen concentration and oxygen desaturation indices (4%ODI) at altitude. Results: Four healthy subjects (3male, age 31 (3) years, body-mass-index 23.6 (0.9) kg/m 2, neck circumference 37.0 (2.7) cm, FEV1 111.8 (5.1)% predicted, FVC 115.5 (6.3)% predicted) were studied. Inspiratory and expiratory muscle strength were normal (PImax 130.7 (29.8) cm H2 O, PEmax (153.3 (38.4) cm H2 O). No subject had significant sleep abnormalities at sea level (Total Sleep Time 344.4 (30.5) mins, Sleep Efficiency 86.6 (6.4)%, Respiratory Disturbance Index 0.8 (0.4)/hour, mean SpO2 97.5 (1.3%). The oxygen desaturation index increased with the development of periodic breathing at altitude (4% ODI 22.0 (7.2)/hour at 3, 380m, 61.4 (26.9)/hour at 4, 370m). Average nocturnal SpO2 (84.8 (0.5%)) at 3, 380m; 81.0 (4.1%) at 4, 370m) and nadir oxygenation (68.1 (8.6%) at 3, 380m; 67.4 (7.6%) at 4, 370m) dropped with altitude. The average EMGdi was 5.2 (19.1%) max at sea level and increased to 14.1 (3.4%) at altitude when falling asleep at 4, 370m, and correlated well with the 4%ODI (r = 0.968, p = 0.032). EMGdi during the last inspiratory effort prior to central apnoea was 5.1 (1.5%) max, while the first inspiratory effort following central apnoea was 10.5 (3.2%) max at 4, 370m. Conclusion: The severity of periodic breathing when asleep deteriorates with an increase in altitude, induced by an elevated neural respiratory drive as a response to hypobaric environmental conditions.